2016
DOI: 10.3991/ijim.v10i1.5276
|View full text |Cite
|
Sign up to set email alerts
|

System Design of Mobile Augmented Book

Abstract: Mobile technologies play an increasingly important role in education. Devices such as smart phones and tablets are becoming powerful tools in the hands for e-Learning, m-Learning and ubiquitous learning. In this paper, the authors propose analysis and design software architecture of a mobile augmented book for in-class and out-class learning. The aim is to improve the quality and usefulness of mobile learning by utilizing a physical book and a mobile device. Requirements, roles, and system architecture are dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Part 3: The System Integration API retrieves information that students accessed previously in service stations. This is in accordance with Saraubon, Nilsook and Wannapiroon [15], who showed that communication between clients' devices and systems consists of data transmission and data retrieval. Further, JSON will be used to support various information such as quizzes, personal data, messages, explanations, etc.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Part 3: The System Integration API retrieves information that students accessed previously in service stations. This is in accordance with Saraubon, Nilsook and Wannapiroon [15], who showed that communication between clients' devices and systems consists of data transmission and data retrieval. Further, JSON will be used to support various information such as quizzes, personal data, messages, explanations, etc.…”
Section: Discussionsupporting
confidence: 90%
“…[14] There are many research related system architecture designs to benefit students. For example, the analysis and design of a mobile augmented book system architecture, for learning inside and outside of the classroom, helped to improve the quality and benefits of learning using mobile devices [15]. The system architecture that is presented here has three layers: a Presentation layer, an Application logic layer and a Data layer.…”
Section: System Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…This reflected that the design of the web-based learning system was in line with the principle and theories of system design [18], and the principle of e-learning design for learning and training [19]. This principle stated that e-learning design should consist of four components: Learning Management System (LMS), Content Management System (CMS), Test Management System (TMS) and Delivery Management System (DMS).…”
Section: Discussionmentioning
confidence: 99%
“…It is easy to engage in the learning process. In addition, mobile learning is also easy to use [12]. The content is clearly arranged and it is easy to understand.…”
Section: Discussionmentioning
confidence: 99%